Pes planovalgus deformity surgical correction in ambulatory children with cerebral palsy - Kadhim, Muayad (Springer Berlin Heidelberg, 2012)
PURPOSE: Planovalgus foot deformity is common in diplegic and quadriplegic patients. Surgery is the definitive treatment to restore the alignment of the talus, calcaneus, and navicular bones. We aimed, in the current study, to compare the effectiveness of subtalar fusion and calcaneal lengthening, and to assess the recurrence in ambulatory children with cerebral palsy. METHODS: This is a retrospective study of 78 patients (138 feet diagnosed with planovalgus deformity) who underwent surgical correction using subtalar fusion or calcaneal lengthening. Range of motion, radiographic indices, kinematic, and pedobarographic data were used to examine the deformity and the outcome of surgery. A repeated measures analysis of variance (ANOVA) was used to test the study hypothesis. RESULTS: Most of the patients were diplegic (87.2 %) and the mean age at surgery was 11.9 ± 2.9 years (range from 4.7 to 18.3 years), with a mean follow-up of 5 ± 4.4 years (range from 1 to 15.4 years). Sixty-three feet were treated with calcaneal lengthening, while 75 were treated with subtalar fusion. The feet treated with subtalar fusion were more severe preoperatively. However, both surgery groups showed improvement postoperatively. Among 12 cases of recurrence, medial column fusion was the main surgery performed to correct the deformity. CONCLUSIONS: Surgery is effective in the treatment of planovalgus deformity in ambulatory children with cerebral palsy. Severe and rigid planovalgus feet can be treated effectively with subtalar fusion. Feet with milder deformity show good results, with calcaneal lengthening. Surgery provides good correction in young patients, but there is a higher recurrence rate. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11832-012-0413-3) contains supplementary material, which is available to authorized users.